2008
DOI: 10.1007/s10735-008-9189-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysectomy and hormonal therapy modulate mK1-immunoreactive duct cells in the mice sublingual glands

Abstract: The immunocytochemical localization of a true tissue kallikrein, mK1, in mouse sublingual glands (SLGs) was examined following hypophysectomy and hormonal replacement therapy. In the glands of intact mice (14 weeks of age), mK1 was detected in the striated ducts (SDs). Full-fledged granular cells were scattered in the SDs of male mice (but not in those of female mice), showing a cellular mosaic distribution of mK1 with some being positive and others being negative. mK1 was also detected in transitional-type gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Administration of hormones (DHT, T 3 , or Dex) restored the phenotype of the GCT-like duct cells, and large secretory granules reappeared. These results suggested that GCT-like duct cells of the mouse SLG are also regulated by hormones, and that androgen and thyroid hormones are necessary for phenotype expression and mK1 synthesis in a mechanism similar to that in the SMG GCT [21].…”
Section: Production Localization and Hormone Dependence Of Mk1 Egfmentioning
confidence: 99%
“…Administration of hormones (DHT, T 3 , or Dex) restored the phenotype of the GCT-like duct cells, and large secretory granules reappeared. These results suggested that GCT-like duct cells of the mouse SLG are also regulated by hormones, and that androgen and thyroid hormones are necessary for phenotype expression and mK1 synthesis in a mechanism similar to that in the SMG GCT [21].…”
Section: Production Localization and Hormone Dependence Of Mk1 Egfmentioning
confidence: 99%
“…A few morphologically similar granular duct cells have also been detected in the SD of the mouse sublingual gland (SLG), usually in males, and rarely in females (4). Such GCTlike cells in the SLG express GCT-specific secretory products (5)(6)(7) and are also up-regulated by pituitary-dependent hormones (7). GCT-like cells were induced in the SD of the SLG in female mice treated with androgen (5).…”
Section: Introductionmentioning
confidence: 99%